1997
DOI: 10.1089/ten.1997.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperature Degradation of a 50:50 Copolymer of PLA-PGA

Abstract: In vitro degradation studies of devices fabricated from polylactic acid (PLA) and polyglycolic acid (PGA) are usually performed at the physiologic 37°C and often take long periods of time to complete. The objective of the present study was to examine the degradation of a 50:50 PLA-PGA copolymer over a wide temperature range (25°C to 80°C) and compare the degradation characteristics at temperatures below and above the polymer's glass transition temperature (T g ). Samples were fabricated using a solvent-casting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 21 publications
8
65
0
Order By: Relevance
“…For PLGA-H, there is not a range of constant energy activation throughout the entire process of thermal degradation. Previous studies presented activation energy of 115 kJ.mol -1 for bulk PLGA 50:50 [18] , 116 kJ.mol -1 for dexamethasone loaded PLGA microspheres 33 indicating that the activation energy value found for PLGA-Mag is close to that demonstrated in these studies. In a general way, both PLGA-H and PLGA-Mag show higher values of activation energy than those of PLGA-R.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For PLGA-H, there is not a range of constant energy activation throughout the entire process of thermal degradation. Previous studies presented activation energy of 115 kJ.mol -1 for bulk PLGA 50:50 [18] , 116 kJ.mol -1 for dexamethasone loaded PLGA microspheres 33 indicating that the activation energy value found for PLGA-Mag is close to that demonstrated in these studies. In a general way, both PLGA-H and PLGA-Mag show higher values of activation energy than those of PLGA-R.…”
Section: Resultssupporting
confidence: 85%
“…However, the degradation of most commonly used PLGA materials is relatively slow at 37 °C, and studies may take several weeks or even years to be completed. Consequently, there is a need to establish techniques to decrease the duration of these studies while ensuring that the results remain relevant and valid 18 . Thermal analytical methods have been widely used in the study of the relationship between a material and its processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Buchholz 8 examined the effect of 2 temperatures, 37-C and 80-C, on the in vitro degradation of D,L -PLA. In another study by Bergsma et al, 10 degradation behavior of L -and D,L -PLA was studied at 90-C. Degradation at temperatures between 25-C and 50-C of polyglycolic acid (PGA) sutures 11 and 50:50 PLGA devices 12 has also been reported. Makino et al 9 reported the degradation of L -and D,L -PLA microcapsules at varying temperatures, ionic strength, and pH of medium.…”
Section: Introductionmentioning
confidence: 98%
“…This was highlighted in the guidelines, which resulted from an American Association of Pharmaceutical Scientists/International Pharmaceutical Federation (AAPS/FIP) sponsored conference on dissolution/in vitro release testing of novel/special dosage forms. 7 Recognizing that drug release is governed by the slowly degrading polymer, research in the past decade has focused on accelerating polymer degradation using elevated temperatures, 8 buffer type, and pH [9][10][11][12][13] and comparing the results to physiologically degraded material. Buchholz 8 examined the effect of 2 temperatures, 37-C and 80-C, on the in vitro degradation of D,L -PLA.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation activation energies obtained were 87.9, 82.7 and 94.9 kJ mol −1 for LC16 : 4, LC18 : 2 and LC9 : 1 respectively. Arrhenius relation has been conducted for the change in several parameters of biodegradable polymers such as molecular weight, breaking strength, viscosity and mass loss [34,38,49,71,72]. The majority of previous publications used change in molecular weight over degradation time at different temperatures.…”
Section: Calculation Of Activation Energymentioning
confidence: 99%